Rod- versus cone-driven ERGs at different stimulus sizes in normal subjects and retinitis pigmentosa patients - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil R. A.; Maguire, John; Murray, I. J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Documenta Ophthalmologica, 2018)
Purpose To study how rod- and cone-driven responses depend on stimulus size in normal subjects and patients with retinitis pigmentosa (RP), and to show that comparisons between responses to full-field (FF) and smaller stimuli can be useful in diagnosing and monitoring disorders of the peripheral retina without the need for lengthy dark adaptation periods.Method The triple silent substitution technique was used to isolate L-cone-, M-cone- and rod-driven ERGs with 19, 18 and 33% photoreceptor contrasts, respectively, under identical mean luminance conditions. Experiments were conducted on five normal subjects and three RP patients. ERGs on control subjects were recorded at nine different temporal frequencies (between 2 and 60 Hz) for five different stimulus sizes: FF, 70A degrees, 60A degrees, 50A degrees and 40A degrees diameter circular stimuli. Experiments on RP patients involved rod- and L-cone-driven ERG measurements with FF and 40A degrees stimuli at 8 and 48 Hz. Response amplitudes were defined as those of the first harmonic component after Fourier analysis.Results In normal subjects, rod-driven responses displayed a fundamentally different behavior than cone-driven responses, particularly at low temporal frequencies. At low and intermediate temporal frequencies (<= 12 Hz), rod-driven signals increased by a factor of about four when measured with smaller stimuli. In contrast, L- and M-cone-driven responses in this frequency region did not change substantially with stimulus size. At high temporal frequencies (>= 24 Hz), both rod- and cone-driven response amplitudes decreased with decreasing stimulus size. Signals obtained from rod-isolating stimuli under these conditions are likely artefactual. Interestingly, in RP patients, both rod-driven and L-cone-driven ERGs were similar using 40A degrees and FF stimuli.Conclusion The increased responses with smaller stimuli in normal subjects to rod-isolating stimuli indicate that a fundamentally different mechanism drives the ERGs in comparison with the cone-driven responses. We propose that the increased responses are caused by stray light stimulating the peripheral retina, thereby allowing peripheral rod-driven function to be studied using the triple silent substitution technique at photopic luminances. The method is effective in studying impaired peripheral rod- and cone- function in RP patients.
Keywords: Rods; Cones; Stimulus size; Electroretinogram; Retinitis pigmentosa